Selection of Trichoderma strains for salinity stress and evaluation for imparting salinity tolerance in sunflower: SELECTION OF TRICHODERMA STRAINS FOR SALINITY AND SALINITY TOLERANCE IN SUNFLOWER - A AZIZ QURESHI; R D PRASAD; A KULKARNI; T NAVANEETA; P LAKSHMAMMA; K S VARAPRASAD; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2018)
The role of Trichoderma fungi in imparting tolerance to various fungal diseases is well known. The idea of this study was to assess the potentiality of Trichoderma in imparting tolerance to abiotic stress, in particular to salinity. In a laboratory study at Indian Institute of Oilseeds Research, Hyderabad, 15 best strains were selected out of 30. Out of the short listed, five potential isolates viz., T. harzianum Th-4d, T. asperellum Ta-v5, T. asperellum Ta-N13, T. asperellum Ta-A5 and T. asperellum Ta-A7 were found prominent towards salt stress tolerance. These were able to grow and sporulate, survived and revived during 7 days of continuous stress up to 1.5 M NaCl concentration in growth medium. Trichoderma isolates Ta-A5 and Ta-A7 recorded highest mean spore count (4.77 logcfu/ml) followed by Ta-N13 > Th-4d >Ta-v5. The significant colony diameter (25.0 mm) at 7th day was observed in isolate Ta-A5. In nutrient broth, the highest sodium concentration in mycelium was recorded in Ta-N13 (860 µg/g) and followed by Th-4d (852 µg/g). In the green house trial, seed priming of sunflower with salinity tolerant isolate Ta-N13 produced highest vigour index (1848) followed by isolates Ta-A5 (1664) and Th-4d (1632). During the field evaluation ofsaline tolerant Trichoderma isolates, it was noticed that isolate Th-4d was found prominent over others when it was seed treated, while Ta-N13 was found effective when it was applied as soil based application in sunflower at 45 days.